Bakhtin and Tolstoy - Ann Shukman (Studies in 20th & 21st Century Literature, 1984)
This article is a study of the way Bakhtin compared and contrasted Dostoevsky and Tolstoy throughout his career. Special attention is given to Bakhtin's two "Prefaces" of 1929 and 1930 to Resurrection and to the dramas in the Collected Literary Works edition of Tolstoy. Bakhtin's view of Tolstoy is not as narrow as is generally thought. Tolstoy is seen as one of many figures of European literature that make up Bakhtin's literary consciousness. He serves as a point of contrast with Dostoevsky and is described as belonging to an older, more rigid, monologic tradition. Bakhtin's prefaces to Tolstoy's works are not just immanent stylistic analyses but can be seen as well as one of the moments when Bakhtin turns to a sociology of style in the wider sense of examining the social-economic conditions that engender style. The prefaces represent a foretaste ofBakhtin's historical poetics of the 1930s.
Keywords: Bakhtin; Dostoevsky; Tolstoy; Prefaces; comparison; Collected Literary Works; literary consciousness; monologic tradition; sociology of style; social-economic; style; historical poetics